All‐in‐one: a robust fluorescent fusion protein vector toolbox for protein localization and BiFC analyses in plants. Issue 6 (28th February 2022) - Han, Jingluan; Ma, Kun; Li, Huali; Su, Jing; Zhou, Lian; Tang, Jintao; Zhang, Shijuan; Hou, Yuke; Chen, Letian; Liu, Yao‐Guang; Zhu, Qinlong
Summary: Fluorescent tagging protein localization (FTPL) and bimolecular fluorescence complementation (BiFC) are popular tools for in vivo analyses of the subcellular localizations of proteins and protein–protein interactions in plant cells. The efficiency of fluorescent fusion protein (FFP) expression analyses is typically impaired when the FFP genes are co‐transformed on separate plasmids compared to when all are cloned and transformed in a single vector. Functional genomics applications using FFPs such as a gene family studies also often require the generation of multiple plasmids. Here, to address these needs, we developed an efficient, modular all‐in‐one (Aio) FFP (AioFFP) vector toolbox, including a set of fluorescently labelled organelle markers, FTPL and BiFC plasmids and associated binary vectors. This toolbox uses Gibson assembly (GA) and incorporates multiple unique nucleotide sequences (UNSs) to facilitate efficient gene cloning. In brief, this system enables convenient cloning of a target gene into various FFP vectors or the insertion of two or more target genes into the same FFP vector in a single‐tube GA reaction. This system also enables integration of organelle marker genes or fluorescently fused target gene expression units into a single transient expression plasmid or binary vector. We validated the AioFFP system by testing genes encoding proteins known to be functional in FTPL and BiFC assays. In addition, we performed a high‐throughput assessment of the accurate subcellular localizations of an uncharacterized rice CBSX protein subfamily. This modular UNS‐guided GA‐mediated AioFFP vector toolkit is cost‐effective, easy to use and will promote functional genomics research in plants.